Attainable region approach in analyzing the breakage behavior of a bed of olivine sand particles: Optimizing impact energy and particle size - Emmanuel E.; Anggraini V.; Syamsir A.; Paul S.C.; Asadi A. (MDPI AG, 2023)
In this study, we investigated the breakage behavior of a bed of olivine sand particles using a drop-weight impact test, with drop weights of various shapes (oval, cube, and sphere). An Attainable Region (AR) technique, which is a model-free and equipment-independent technique, was then applied to optimize the impact energy during the breakage process and also to get particles in defined particle size classes. The findings revealed that the different drop weights produce products within the three different particle size classes (feed, intermediate, and fine). A higher mass fraction of materials in the fine-sized class (?75 m) was obtained when the spherical drop weight was used relative to the cubic and oval drop weights. The drop height was found to have a significant influence on the breakage process. The AR technique proved to be a practical approach for optimizing impact energy and particle size during the breakage of a bed of olivine particles, with potential application in sustainable soil stabilization projects. 2020 by the authors. Licensee MDPI, Basel, Switzerland.